Effect of elevated fasting blood glucose level on the 1‐year mortality and sequelae in hospitalized COVID‐19 patients: A bidirectional cohort study. Issue 7 (19th April 2022) - Chai, Chen; Chen, Kui; Li, Shoupeng; Cheng, Gang; Wang, Wendan; Wang, Hongxiang; Wei, Dunshuang; Peng, Cao; Sun, Qi; Tang, Zehai
Abstract: To observe the predictive effect of fasting blood glucose (FBG) level on the prognosis, clinical sequelae, and pulmonary absorption in hospitalized coronavirus disease 2019 (COVID‐19) patients with and without a history of diabetes, respectively, and to evaluate the correlation between the dynamic changes of FBG and poor prognosis. In this bidirectional cohort study, we enrolled 2545 hospitalized COVID‐19 patients (439 diabetics and 2106 without a diabetic history) and followed up for 1 year. The patients were divided according to the level of admission FBG. The dynamic changes of FBG were compared between the survival and the death cases. The prediction effect of FBG on 1‐year mortality and sequelae was analyzed. The 1‐year all cause mortality rate and in‐hospital mortality rate of COVID‐19 patients were J‐curve correlated with FBG ( p < 0.001 for both in the nondiabetic history group, p = 0.004 and p = 0.01 in the diabetic history group). FBG ≥ 7.0 mmol/L had a higher risk of developing sequelae ( p = 0.025) and have slower recovery of abnormal lung scans ( p < 0.001) in patients who denied a history of diabetes. Multivariable Cox regression analysis showed that FBG ≥ 7.0 mmol/L was an independent risk factor for the mortality of COVID‐19 regardless of the presence or deny a history of diabetes (hazard atio [HR] = 10.63, 95% confidence interval [CI]: 7.15−15.83, p < 0.001; HR = 3.9, 95% CI: 1.56−9.77, p = 0.004, respectively). Our study shows that FBG ≥ 7.0 mmol/L can be a predictive factor of 1‐year all‐cause mortality in COVID‐19 patients, independent of diabetes history. FBG ≥ 7.0 mmol/L has an advantage in predicting the severity, clinical sequelae, and pulmonary absorption in COVID‐19 patients without a history of diabetes. Early detection, timely treatment, and strict control of blood glucose when finding hyperglycemia in COVID‐19 patients (with or without diabetes) are critical for their prognosis.